Stereotactic Ablative Radiotherapy for the Treatment of Refractory Cardiac Ventricular Arrhythmia. (June 2015) - Loo, Billy W.; Soltys, Scott G.; Wang, Lei; Lo, Anthony; Fahimian, Benjamin P.; Iagaru, Andrei; Norton, Linda; Shan, Xin; Gardner, Edward; Fogarty, Thomas; Maguire, Patrick; Al-Ahmad, Amin; et al.
Abstract : Supplemental Digital Content is available in the text.